Exploring the causes and effects of oversupply materials through MRP: A general review - Nadarajan, Santhirasegaran; Chandren, Sitraselvi; Mohd Nawi, Mohd Nasrun (2013)
This paper will address the phenomena arising from the oversupply materials that actually explode from the Material Requirements Planning (MRP).This system basically supports the operations especially the inventory control system and have become the most reliable in managing stocks effectively.MRP has all it years facing problems and challenges even though 35 years is far too long through adoption of supply chain management techniques.However, concerning the issue on oversupply materials still unresolved and require more in depth solution.The objective of this paper, as far as concern research on oversupply is not been investigated before and this may inject the new idea for the extension of literature on oversupply and MRP. The review will look into identifying the causes and effects of oversupply associating with MRP.How this problem has an impact on the operations efficiency especially the inventory control system?